If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 2x + 5 = 3 Reorder the terms: 5 + 2x + 5y = 3 Solving 5 + 2x + 5y = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + 2x + -5 + 5y = 3 + -5 Reorder the terms: 5 + -5 + 2x + 5y = 3 + -5 Combine like terms: 5 + -5 = 0 0 + 2x + 5y = 3 + -5 2x + 5y = 3 + -5 Combine like terms: 3 + -5 = -2 2x + 5y = -2 Add '-5y' to each side of the equation. 2x + 5y + -5y = -2 + -5y Combine like terms: 5y + -5y = 0 2x + 0 = -2 + -5y 2x = -2 + -5y Divide each side by '2'. x = -1 + -2.5y Simplifying x = -1 + -2.5y
| 4*3r=27 | | x^3+x^2+36x+36= | | 2x^2+5x=36 | | t^2-6t+-15=0 | | 3x^2-5y^2=3 | | 3+2*5-7= | | -8(x+4)=2(x-4) | | 2x-x+4+2=8-2 | | -5(-4x+1)=-16x-7 | | 4-3Inx=5 | | -5(x-6)=-6(x+9) | | 3a=28b | | 2(4x+5)=-8x | | 4k^2+17k+18= | | t/b-s/b=1b= | | -4(5x+7)=-9x | | t/b-s/b=1 | | 2y^2-2y+3= | | 57-3x=21 | | 4n^3+13n+3= | | -9(-2x-9)=-4x | | -5(5x-3)=-3x+5 | | (-20)/(-4)= | | -3x=4x+3 | | -3(x+9)=6(x-3) | | -10x=9x+6 | | -10x=9x | | c^2-5cf-24f^2=0 | | 15u^2-37u+18=0 | | 2(-3x-1)=-14x+8 | | 3c-7c=22 | | x^2+y^2-6x+4y+11=0 |